Anion inhibition studies of a beta carbonic anhydrase from the malaria mosquito Anopheles gambiae - Daniela Vullo; Leo Syrjänen; Marianne Kuuslahti; Seppo Parkkila; Claudiu T. Supuran (Taylor & Francis Group, 2018)
An anion inhibition study of the β-class carbonic anhydrase, AgaCA, from the malaria mosquito Anopheles gambiae is reported. A series of simple as well as complex inorganic anions, and small molecules known to interact with CAs were included in the study. Bromide, iodide, bisulphite, perchlorate, perrhenate, perruthenate, and peroxydisulphate were ineffective AgaCA inhibitors, with KIs > 200 mM. Fluoride, chloride, cyanate, thiocyanate, cyanide, bicarbonate, carbonate, nitrite, nitrate, sulphate, stannate, selenate, tellurate, diphosphate, divanadate, tetraborate, selenocyanide, and trithiocarbonate showed KIs in the range of 1.80-9.46 mM, whereas N,N-diethyldithiocarbamate was a submillimolar AgaCA inhibitor (KI of 0.65 mM). The most effective AgaCA inhibitors were sulphamide, sulphamic acid, phenylboronic acid and phenylarsonic acid, with inhibition constants in the range of 21-84 µM. The control of insect vectors responsible of the transmission of many protozoan diseases is rather difficult nowadays, and finding agents which can interfere with these processes, as the enzyme inhibitors investigated here, may arrest the spread of these diseases worldwide.